Financial management - Chadwick, Leslie; Kirkby, Donald (London : Routledge, 1994)
Overview. Obtaining the finance. Investing the finance. Evaluating performance. Control. Other topics.
Keywords: Finance; Business enterprises; Corporations; Corporations -- Finance; Business enterprises -- Finance -- Case studies